MATHEMATICAL MODELLING OF TRANSIENTS IN THE ELECTRIC DRIVE OF THE SWITCH – THE MAIN EXECUTIVE ELEMENT OF RAILWAY AUTOMATION - S. G. Buriakovskyi (National Technical University "Kharkiv Polytechnic Institute", 2020)
Goal. To develop a mathematical and imitation model of the electric drive of the railroad switch as a two- and three-mass electromechanical system based on DC and AC motors as the main executive element of railway automation. The modelling is based on the parameters of the SP-6m switches as the main modification of the executive element of the Ukrainian domestic railways automation system. Methodology. The authors have presented the mechanical part of the railroad switch as a three-mass construction scheme with serial connection of elastic masses. Special attention is paid to the character of the movement of the switch point tongues, when describing them in the form of two- and three- mass kinematic schemes, as well as to the mechanical state of the traction and connections as nodes, which are most sensitive to the negative effects of some modes of the railroad switch. Results. A simulation mathematical model of SP-6m switch for AC and DC motors, which allows to study the influence of various factors, has been developed and tested at the stand of the Automation Laboratory of the Ukrainian State University of Railway Transport, Kharkiv. The deviation in the basic parameters of the switch translation process is less than 5 %. Originality. For the first time a mathematical model of an electric drive of the railroad switch is developed, which takes into account elastic relations and load characteristics as an object of controlling the speed of movement of switch point tongues. Practical significance. We have created a mathematical model of the electric drive of the railroad switch which allows to examine the influence of various factors, including the influence of the environment on the operation of the switch.